2017
DOI: 10.1007/978-981-10-6547-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Genomic Targets of Alkylating Polyamide Conjugates Using High-Throughput Sequencing

Abstract: Chemically engineered small molecules targeting specific genomic sequences play an important role in drug development research. Pyrrole-imidazole polyamides (PIPs) are a group of molecules that can bind to the DNA minor-groove and can be engineered to target specific sequences. Their biological effects rely primarily on their selective DNA binding. However, the binding mechanism of PIPs at the chromatinized genome level is poorly understood. Herein, we report a method using high-throughput sequencing to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Extensive analysis of the cognate binding sites clearly showed that SAHA–PIP G binds to the WSWSW motif as expected based on the structure and the predicted binding rule of PIP. So far, PIP binding specificity has been demonstrated using cell extracts (Chandran et al, 2016). Therefore, this is the first confirmation that SAHA–PIP could specifically recognize its binding sequence not only in vitro but also at the genome‐wide level in cells, thereby implying the potential use of PIP for site‐specific regulation of genes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive analysis of the cognate binding sites clearly showed that SAHA–PIP G binds to the WSWSW motif as expected based on the structure and the predicted binding rule of PIP. So far, PIP binding specificity has been demonstrated using cell extracts (Chandran et al, 2016). Therefore, this is the first confirmation that SAHA–PIP could specifically recognize its binding sequence not only in vitro but also at the genome‐wide level in cells, thereby implying the potential use of PIP for site‐specific regulation of genes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide binding of these tripartite molecules is captured by photo-induced crosslinking followed by biotin-enabled enrichment and unbiased NGS sequencing of the conjugated genomic loci [23,24]. The ability to induce rapid crosslinking at the desired time point distinguishes COSMIC-seq from continuous and uncontrolled alkylation-dependent DNA conjugations that have been used to query genome-wide binding of polyamides [25].…”
Section: An Im/py Pair Binds G•c; Py/im Binds C•g and Py/py Pairs Bomentioning
confidence: 99%